Fig. 3 in Oysters (Bivalvia: Ostreidae And Gryphaeidae) Recorded From Malaysia And Singapore ... - Lam, Katherine; Morton, Brian (Zenodo, 2009)
Fig. 3. Crassostrea gigas (Thünberg, 1793) from Johor Strait, Malaysia (NHM20090290). A, external view of the right shell valve, B, external view of the left shell valve. C, internal view of the right shell valve D, internal view of the left shell valve. ... : Published as part of Lam, Katherine & Morton, Brian, 2009, Oysters (Bivalvia: Ostreidae And Gryphaeidae) Recorded From Malaysia And Singapore, pp. 481-494 in Raffles Bulletin of Zoology 57 (2) on page 486, DOI: 10.5281/zenodo.5342232 ...